2003
DOI: 10.2151/jmsj.81.1435
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Covariance between Japan Summer Precipitation and Western North Pacific SST

Abstract: A statistical analysis is conducted of the covariance between summer precipitation in Japan and concurrent variations of sea surface temperature (SST) in the Western North Pacific (WNP;. To this end, a singular value decomposition (SVD) is applied to observed monthly anomalies of the two fields for the period 1961-1998 (38 summer seasons).The first coupled mode of the SVD explains as much as 71% of the total cross-covariance between WNP SST and Baiu precipitation. It is characterized by a zonally elongated dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Due to the drought susceptibility of the plants with large stomata, only those species occurring in humid habitats can sustain larger genomes [56, 58]. Compared with the monsoonal climate which is characterized by obvious precipitation seasonality in subtropical China and the Himalayas [59, 60], the maritime climate of the Japan islands [61] would create relatively more humid habitats that facilitate the evolution of P. japonica toward genomic gigantism.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the drought susceptibility of the plants with large stomata, only those species occurring in humid habitats can sustain larger genomes [56, 58]. Compared with the monsoonal climate which is characterized by obvious precipitation seasonality in subtropical China and the Himalayas [59, 60], the maritime climate of the Japan islands [61] would create relatively more humid habitats that facilitate the evolution of P. japonica toward genomic gigantism.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of summer SSTs over the Sea of Japan on heavy precipitation has not yet been examined, despite the particular sea being one of the hot spots of global SST warming (Japan Meteorological Agency, ; Wu et al, ). In fact, a statistical analysis based on monthly and/or seasonal mean fields showed negative correlation between monthly anomalies in summertime precipitation over Japan and SSTs over the surrounding oceans, including the East China Sea, the Sea of Japan, and the Kuroshio‐Oyashio Extension region (Fukutome et al, ). The enhanced descending motion associated with the Bonin High, a summertime subtropical anticyclone over the western North Pacific, causes prevailing hot sunny conditions over Japan accompanied by increased SSTs (Enomoto et al, ), and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…It then gradually retreats in September (e.g., Kang et al 1999;Lau 1992). Fukutome et al (2003) identified the particular sea surface temperature (SST) correlation feature with the variation of summer precipitation in Japan. They showed that the SST pattern displays a zonally elongated dipole with opposite SST anomalies on either side of approximately 30°N.…”
Section: Introductionmentioning
confidence: 99%